Działalność koordynacyjna rad narodowych w stosunku do spółdzielczości. Problemy prawne: [Coordinating activities of the people’s councils in the context of cooperation legal problems] (Studia Prawnicze / The Legal Studies, 1964)
The first part of the article is devoted to the general concept of coordination and the role of the people’s councils in coordinating activities. The author states that the position and scope of activities of the people’s councils as local government bodies fully determine their key role in the coordination functions carried out both within the apparatus of the people’s councils and in relation to institutions directly subordinated to the people’s councils (“internal coordination”), and in relation to entities not directly subordinated to the people’s councils (“external coordination”). In the first case, the concept of coordination is deeply intertwined with the broader legal concepts of leadership and supervision while the “external coordination” is carried out using a number of special legal measures.The second part of the article describes the impact on the state cooperation in general and the cooperation of the people’s councils in particular. In a socialist system, cooperation should be included in the system of planned economy and, as a consequence, be subject to the general government management. At the same time, given the fact that cooperation is a self-governing social movement, the means of this management must be selected in such a way that they do not violate the organizational independence of cooperatives.As the purpose of the state influence on cooperation is to include it in the planned economy, the main base for this influence is coordination. The people’s councils have especially many opportunities at their disposal to correctly influence on cooperation; it is due to the fact that both the organization and the forms of activity of the people’s councils have a social element. From this point of view, we can talk about some homogeneity of the people’s councils and cooperative organizations as forms of mass participation in state and public life. The forms of activity of the people’s councils determined by their representative nature (public control, social and organizational activity) provide the council apparatus with the opportunity to have influence on the affairs of the cooperatives as a whole without violating their organizational independence.The third part of the article analyses the specific legal means of coordination available to the people’s councils in relation to cooperation. The subject of the analysis: the impact of the people’s councils on the organizational affairs of cooperatives (creation, liquidation and change of the Charter); the influence of the people’s councils on the development of economic and financial plans for cooperatives; the use of general coordination means relating to cooperatives provided for by the law on the people’s councils, and the “indirect” coordinating activity of their apparatus which is expressed in the establishment of the cooperation obligations towards the state and in the provision of state aid to cooperatives.The last part of the article is devoted to the review of the relationship between the people’s councils and cooperation in practice and the subsequent conclusions in terms of the law provisions that should have been published. The author expresses the opinion that the people’s councils should be given the opportunity to impact on the fulfilment of the economic and financial plans by the cooperatives. This impact should be expressed in the provision of state aid to cooperatives, and this aid should depend on the plan fulfilment by the cooperatives.